2019
DOI: 10.2147/dmso.s209147
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and socio-behavioral factors associated with sugar-sweetened beverages consumption among 15 years and older persons in South Africa</p>

Abstract: Objective: The aim of this study was to assess the frequency of sugar-sweetened beverages (SSB) consumption and its relationship with socio-behavioral factors using national population-based data in South Africa. Subjects and methods: Cross-sectional data were analyzed from the South African National Health and Nutrition Examination Survey (SANHANES-1) in 2012. The population sample included 15,179 adults (median age=34.0 years, interquartile range=25, range=15–98 years) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…This finding is consistent with research from Singapore showing that high and medium earners consumed less soft drinks when compared to low earners 11 . Conversely, a study from Australia reported that households with higher annual incomes were more likely to consume soft drinks compared to households with lower annual incomes 23 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with research from Singapore showing that high and medium earners consumed less soft drinks when compared to low earners 11 . Conversely, a study from Australia reported that households with higher annual incomes were more likely to consume soft drinks compared to households with lower annual incomes 23 .…”
Section: Discussionmentioning
confidence: 91%
“…The findings of the present study are consistent with findings from Malaysia showing that 53.3% of individuals consume soft drinks three times per week or more 20 , with similar findings also in Saudi Arabia (40%) and Nigeria (42.8%). Daily consumption has been reported in developed countries such as the USA (40%) 21 and the UK (20.4%) 22 and similarly in South Africa (48.3%) 23 . This may be related to the culture of western and European countries preferring fast food and artificially sweetened soft drinks.…”
Section: Discussionmentioning
confidence: 97%
“…We found that a very high proportion of ASEAN university students (82%) consumed SSBs daily, which were much higher than that reported in another study in university students in LMICs (35%) [ 12 ]. The frequent consumption of SSBs is worrisome, as research showed that it contributed to negative dietary patterns, including frequent fast food, high salt, and low fruit and vegetable intake [ 14 ]. Our findings also suggested that from the first year of university life onwards, students, particularly those living off campus, demonstrated increasingly poorer dietary choices.…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of university students consumed insufficient fruit and vegetable daily [ 8 , 12 , 13 ]. More than one-third (35%) of university students in five ASEAN countries consumed sugar-sweetened beverages (SSBs) once or more times daily [ 14 ]. Apart from these health-risk behaviors, mental well-being is also a neglected health issue among ASEAN university students.…”
Section: Introductionmentioning
confidence: 99%
“…‘How many fruits do you usually eat per day?’ Vegetable intake . ‘How many portions of vegetables, excluding potatoes, do you usually eat per day?’ Response options ranged from 1 = 4 or more per day to 5 = none (Pengpid & Peltzer, 2019, p. 938).…”
Section: Methodsmentioning
confidence: 99%